Faktor – Faktor yang Mempengaruhi Komplikasi pada Pasien Diabetes Mellitus di RSUD Dr. Moewardi - Tista Ayu Fortuna; Hidayah Karuniawati; Desti Purnamasari; Devi Etivia Purlinda (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Diabetes Mellitus (DM) is a disease characterized by hyperglycemia and disturbances in the metabolism of carbohydrates, fats, and proteins associated with absolute or relative deficiencies of insulin action and or secretion. The main problem for DM sufferers is that more than 50% of diabetic patients do not know about the disease and its complications, so patients will return to the hospital with high blood glucose levels accompanied by various complications. The study aims to determine the factors that can cause complications in patients with diabetes mellitus. This research is a non-experimental study with a cross-sectional approach. The data were analyzed using SPSS with a Chi-square or Kruskal-Wallis and multivariate logistic regression test. Body mass index and duration of diabetes are significantly associated with the incidence of complications (p-value 0.05). Patients with an abnormal body mass index are 4.184x more at risk of complications than patients with a normal body mass index (RR 4.184 CI 1.581 – 11.070). In addition, patients with diabetes duration ≥5 years were 4.121 times more at risk of complications than patients with diabetes durations 5 years (RR 4.121 CI 1.570 – 10.816). The most common complication suffered by diabetic patients in this study was hypertension in 46 patients (41%), and the most common therapeutic regimen received by patients was oral hypoglycemia in 50 patients (52%).